Menyiapkan Generasi Muda Sigap Menghadapi Bencana Tanah Longsor - A. M Indriani; G. Utomo; F. Harami; Y. Az'zahra; A. Sani; N. Firna; A. Octavia; T.A. Rachman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Landslides are one of the natural disasters that have had a wide range of social and economic consequences, including damage to public infrastructure, transportation, and telecommunications, as well as deaths Public understanding of disaster prevention, early sign of a disaster, how to handle it during, and after a disaster occurs is still low so it is necessary to educate the public to minimize losses. Preparing a young generation who is strong in dealing with landslides must be done early so that the community has preparedness when this disaster occurs. The students of SMP PGRI 2 and SMP Negeri 4 Balikpapan City were chosen to receive education, considering that the location of this school is in an area that has a high potential for landslides because the area has a steep contour and is a densely populated area. Before and after education, a test was conducted to determine the level of students' understanding of the prevention and management of landslides.